Full-Potential Electronic Structure Method Energy and Force Calculations with Density Functional and Dynamical Mean Field Theory - Wills, John M. (Springer Series in Solid-State Sciences,, 2010)
This book covers the theory of electronic structure of materials, with special emphasis on the usage of linear muffin-tin orbitals. Methodological aspects are given in detail as are examples of the method when applied to various materials. Different exchange and correlation functionals are described and how they are implemented within the basis of linear muffin-tin orbitals. Functionals covered are the local spin density approximation, generalised gradient approximation, self-interaction correction and dynamical mean field theory.